SQUID-based detection of ultra-low-field multinuclear NMR of substances hyperpolarized using signal amplification by reversible exchange. Issue 1 (December 2017) - Buckenmaier, K.; Rudolph, M.; Back, C.; Misztal, T.; Bommerich, U.; Fehling, P.; Koelle, D.; Kleiner, R.; Mayer, H.; Scheffler, K.; Bernarding, J.; Plaumann, M.
Abstract Ultra-low-field (ULF) nuclear magnetic resonance (NMR) is a promising spectroscopy method allowing for, e.g., the simultaneous detection of multiple nuclei. To overcome the low signal-to-noise ratio that usually hampers a wider application, we present here an alternative approach to ULF NMR, which makes use of the hyperpolarizing technique signal amplification by reversible exchange (SABRE). In contrast to standard parahydrogen hyperpolarization, SABRE can continuously hyperpolarize 1 H as well as other MR-active nuclei. For simultaneous measurements of 1 H and 19 F under SABRE conditions a superconducting quantum interference device (SQUID)-based NMR detection unit was adapted. We successfully hyperpolarized fluorinated pyridine derivatives with an up to 2000-fold signal enhancement in 19 F. The detected signals may be explained by two alternative reaction mechanisms. SABRE combined with simultaneous SQUID-based broadband multinuclear detection may enable the quantitative analysis of multinuclear processes.